Use of 16S rRNA gene sequencing for prediction of new opportunistic pathogens in chicken ileal and cecal microbiota - Kollarcikova, Miloslava; Kubasova, Tereza; Karasova, Daniela; Crhanova, Magdalena; Cejkova, Darina; Sisak, Frantisek; Rychlik, Ivan (Poultry science, 2019)
In this study, we addressed differences in the development of gut microbiota in 4 successive batches of commercially hatched broiler parent chickens. When planning this study, we expected to find a batch with compromised performance which would allow identification of microbiota of suboptimal composition. Microbiota composition was determined only by sequencing the V3/V4 region of 16S rRNA genes in samples collected from chickens 5 to 18 wk of age. In a total, 100 and 160 samples originating from the ileum or cecum were processed, respectively. In one of the flocks with suboptimal performance we identified an increased abundance of Helicobacter brantae forming over 80% of ileal microbiota in individual chickens. Moreover, we also tested samples of 53-wk-old hens from the same genetic line in which egg production decreased. In this case, cecal microbiota was enriched for Fusobacterium mortiferum forming over 30% of total cecal microbiota. Although none of the identified unusual microbiota members have been well recognized as pathogenic, they may represent new opportunistic pathogens of chickens worth of further investigation. Analysis of gut microbiota composition by next generation sequencing thus proved as a useful and unbiased alternative to bacterial culture, especially in the cases of unspecific symptoms like decrease in flock performance.
Keywords: kur domácí; sekvenční analýza RNA; bakteriální RNA; microbiota; broiler parent flock; Helicobacter; Chickens; RNA, Ribosomal, 16S; Bacteria; cékum; Gastrointestinal Microbiome; caecum; Cecum; střevní mikroflóra; ileum; Animals; ženské pohlaví; Ileum; zvířata; RNA ribozomální 16S; Fusobacterium; Sequence Analysis, RNA; Female; RNA, Bacterial; chicken